Manajemen Layanan Pendidikan dalam Meningkatkan Kepuasan Siswa di MAN 3 Pekanbaru - Assa, Liya Zaki; Fitriyani, Cindy; Yurisman, Depri (Jurnal Pendidikan Madrasah, 2026)
This study is motivated by the suboptimal management of educational services in madrasahs in meeting student satisfaction, as indicated by the gap between provided services and student expectations, particularly in administrative services, facilities, and service evaluation. The study aims to analyze educational service management in improving student satisfaction at MAN 3 Pekanbaru, covering planning, implementation, evaluation, and the level of student satisfaction. This research employs a qualitative approach with a descriptive method using observation, in-depth interviews, and documentation techniques. Data analysis applies to an interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that service planning is systematic but still top-down, implementation is adequate in learning but weak in administrative and technological aspects, evaluation is not yet based on systematic student satisfaction measurement, and student satisfaction is relatively high in teacher interaction but low in administrative services and facilities.